2017
DOI: 10.1016/j.econlet.2017.06.007
|View full text |Cite
|
Sign up to set email alerts
|

New global estimates of child poverty and their sensitivity to alternative equivalence scales

Abstract: This paper uses micro-data from household surveys from 89 countries to estimate the rate of extreme poverty among children in the developing world. 19.5 percent of children are estimated to live on less than $1.90 per day, as opposed to 9.2 percent of adults. Poverty rates for children remain above 17 percent, and are greater than adult poverty rates, for all reasonable two-parameter equivalence scales.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 15 publications
(14 reference statements)
2
17
0
Order By: Relevance
“…Over one in five girls and boys ages 0-14 live in a poor household and they represent 44 percent of the poor population. As already documented by Newhouse et al (2017) using the same dataset, 19.5 percent of all children younger than 18 are estimated to live on less than $1.90 per day, a bit over double the estimate for adults (9.2 percent). Girls and boys are consistently poorer than adults and seniors, and poverty is higher for children younger than 5 years of age, regardless of sex 22 .…”
Section: Gender Profiles Of the Poorsupporting
confidence: 53%
“…Over one in five girls and boys ages 0-14 live in a poor household and they represent 44 percent of the poor population. As already documented by Newhouse et al (2017) using the same dataset, 19.5 percent of all children younger than 18 are estimated to live on less than $1.90 per day, a bit over double the estimate for adults (9.2 percent). Girls and boys are consistently poorer than adults and seniors, and poverty is higher for children younger than 5 years of age, regardless of sex 22 .…”
Section: Gender Profiles Of the Poorsupporting
confidence: 53%
“…With the assumption that economies of scale exist in household consumption and the concerns of self-employed households, our estimates might profile extreme poverty in developed nations more accurately. Similar to the patterns reported by Newhouse et al (2017), we found that child poverty rates are higher than adult poverty ratios in all countries studied, regardless of which equivalence scale is used. That being said, it is demonstrated that 1 in 30 children in the US experiences homelessness every year (Bassuk et al 2014).…”
Section: Discussionsupporting
confidence: 88%
“…Batana, Bussolo, and Cockburn (), in a study of 73 countries, find that poverty rates fall significantly and especially among different age groups when using per capita estimates compared with estimates that use adult equivalence scales. Newhouse, Bercerra and Evans () found that the dominance of child poverty is consistent irrespective of equivalence scales and absolute levels of adult poverty vary significantly by the estimators unlike child rates. Overall, there appears to be little consensus on whether one approach to measuring poverty dominates another or under what conditions the choice of measurement is dependent upon household structure.…”
Section: Background and Introductionmentioning
confidence: 98%